The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.12938/bifidus1982.7.2_61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isomalto-oligosaccharides on Human Fecal Flora

Abstract: The effect of isomalto-oligosaccharides on human fecal flora was studied. Bifidobacteria and the Bacteroides fragilis group from human intestine could utilize isomalto-oligosaccharides but Escherichia coli and other bacteria could not. After the administration of isomaltooligosaccharides (13.5 g daily for 2 weeks) to healthy adult men and senile persons, the numbers of bifidobacteria in the feces increased. The consistency of feces was improved. These studies may support the usefulness of isomalto-oligosacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 8 publications
4
80
0
Order By: Relevance
“…However, no change was seen in SCF in either variable. Consequently, these results agreed with that of Kohmoto et al 4, who found that IMO were nearly 85% digested. Moreover, Cervantes-Pahm et al 8 and Kendall et al 9 found virtually no digestion in SCF, both in vivo and in vitro.…”
Section: Blood Glucose and Insulin Responsessupporting
confidence: 92%
See 2 more Smart Citations
“…However, no change was seen in SCF in either variable. Consequently, these results agreed with that of Kohmoto et al 4, who found that IMO were nearly 85% digested. Moreover, Cervantes-Pahm et al 8 and Kendall et al 9 found virtually no digestion in SCF, both in vivo and in vitro.…”
Section: Blood Glucose and Insulin Responsessupporting
confidence: 92%
“…Isomaltooligosaccharides primarily derive from exposure of the maltose-rich syrup to the transglucosidase enzyme 4 resulting in an isomaltose-rich syrup, high in digestion-resistant 1,6 alpha bond linkages. In vitro resistance to pancreatic enzyme digestion has led nutrition companies to list IMO as a fibre.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the growth activity of bifidobacteria in the human intestines increased in proportion to the degree of glucosidic polymerization of the IMO components. The results of an in vitro utilization test by bifidobacteria 1) show that no significant difference in growth activity was apparent between the disaccharide components of IMO such as isomaltose, and the trisaccharide components such as panose and isomaltotriose. In addition, it has been shown that IMO could be characterized as partially digestible from rat and human intake tests.…”
Section: As Shown Inmentioning
confidence: 95%
“…Using ex-glucosidase and neopullulanase, several researchers 8 ,9) produced sugar mixtures containing isomaltose that act as growth factors for bifidobacteria in vitro and in vivo. 10) Sawai et al, [11][12][13][14][15] reported numerously on enzymatic properties of an isomaltodextranase (EC 3.2.1.94) from Arthrobacter globiformis T6; 1) successive release of isomaltose from nonreducing ends of dextran and isomaltooligosaccharides, 2) the substrate specificity of hydrolysis on isomaltosylex(l ~ 2), ex(l ~ 3), ex(l ~4), and ex(l ~6) linkages, and 3) transfer and condensation activities on isomaltose to produce isomaltotetraose. Therefore, applications of the transfer action of isomaltodextranase will be able to produce various transfer products having isomaltosyl residues, some novel.…”
mentioning
confidence: 99%